Performance Analysis of LDR, Photodiode, and BH1750 Sensors for Sunlight Intensity Measurement in Open Areas - Shiddiqy, Muhammad Iqbal Ash; Sunardi, Sunardi (Association for Scientific Computing Electrical and Engineering (ASCEE), 2024)
Light, as an electromagnetic phenomenon, can be elucidated as both a wave and a particle. The wave-particle duality portrays light as an electromagnetic wave and discrete particles known as photons. The spectrum of light represents the wavelength in a visual array of colors. Optics, a vital field in physics, delves into the characteristics of light. Light, an electromagnetic wave with a wavelength of 380-750 nm, exhibits dual nature as both a wave and a particle. Light intensity is measured in lumens or lux, indicating the strength of a light source in a specific direction per unit angle. The human eye, sensitive to the visible light spectrum, holds significance in optics and photometry. Light sensors such as LDR, Photodiode, and BH1750 sensor transform light information into electronic signals for electronic devices like the Arduino Uno microcontroller. The research was methods by measuring light intensity for 5 days at 3 different times (morning, noon and afternoon) simultaneously and open area. The parameters that form the basis of the comparison include error values, stability in the calibration process, light intensity measurement range, and sensor price. Data was collected at the same time during the day to ensure consistent test conditions. Based on the research findings, the BH1750 sensor was selected as the most effective among the three sensors used, exhibiting the smallest average error value of 0.755%. It is easily calibrated, has a wide intensity measurement range (0-65535 lux), and comes at a relatively affordable price.